First Derivative Synchronous Spectrofluorimetric Quantification of Telmisartan/Amlodipine Besylate Combination in Tablets - Neeli, Sirisha; Anuganti, Haripriya; Puvvadi, Sathesh Babu R; Subrahmanyam, Chavali VS (Dhaka University Journal of Pharmaceutical Sciences, 2013)
A first derivative synchronous spectrofluorimetric method has been developed and validated for simultaneous determination of telmisartan (TEL) and amlodipine besylate (AML) in combined tablet dosage form without any prior separation of components from the sample. TEL was determined at emission wavelength of 675 nm (zero-crossing wavelength point of AML). Similarly, AML was measured at 458 nm (zero-crossing wavelength point of TEL). The first derivative amplitude- concentration plots were rectilinear over the range of 4-14 ?g/ml for TEL and 1-6 ?g/ml for AML. The method was validated statistically as per ICH guidelines. Limit of detection (LOD) and quantification (LOQ) are reported. The % assay in commercial formulation was found to be in the range 99.60 100.22 and 98.40 99.80 for TEL and AML, respectively by the proposed method and % RSD values for precision and accuracy studies were found to be less than 2. The proposed method can be successfully applied for routine analysis of TEL and AML in tablets. Dhaka Univ. J. Pharm. Sci. 12(1): 35-40, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16298